Critical Thinking Skills of Prospective Elementary School Teachers in Integrated Science-Mathematics Lectures - Yanti Fitria; Fiddinya Nurul Hasanah; Nurhizrah Gistituati (Journal of Education and Learning (EduLearn), 2018)
The purpose of this study is to find out the critical thinking skills indicators and aspects of prospective elementary school teachers in mathematics-science integration lectures on electrical circuits and mathematical logic lesson. This research uses random sampling technique in which 30 first semester students were chosen randomly from one of university in Padang region West Sumatera Indonesia. This research uses Research and Development (R and D). The critical thinking skills are seen from processes, observations, and tests. The process of critical thinking skills of prospective elementary school teachers on the average of critical thinking skills indicator is 84% in strategies and tactics, 80% in advanced clarification and 83% in elementary clarification, basic support, and inference. The result of observing the critical thinking skills of prospective elementary school teachers on the average of each lectures is significantly increased to be 81.9%. The results of pre-test and post-test were increased significantly. It is shown from N-gain of 0.7 to be medium category.